Parameters affecting baseline hip function in patients with cam-derived femoroacetabular impingement syndrome: data analysis from the German Cartilage Registry - Serong, Sebastian; Schutzbach, Moritz; Fickert, Stefan; Niemeyer, Philipp; Sobau, Christian; Spahn, Gunter; Zinser, Wolfgang; Landgraeber, Stefan (Journal of orthopaedics and traumatology, 2021)
Using the database of the German Cartilage Registry (KnorpelRegister DGOU), this study aims to present patient- and joint-related baseline data in a large cohort of patients with cam-derived femoroacetabular impingement syndrome (FAI) and to detect symptom-determining factors.
Gesehen am 05.05.2022